Students’ Imaginative Skills to Create a Simple Gamification on Chemistry Material - Nelius Harefa; Sumiyati Sumiyati (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
The creativity dimension related to cognitive, affective, psychomotor and other skills aspects. The creativity dimension is closely related to learning outcomes and students' ability to be creative in producing relevant products. One important indicator of the creativity dimension is students' imagination skills. Through good imagination skills, students will be able to predict and create patterns in the content and context of learning material. In this research, an analysis of students' imagination skills will be carried out which consists of three indicators, namely playing with possibilities, making connections, and using intuition. The research was carried out using a classroom action research approach consisting of 3 cycles, where research data was collected by giving a questionnaire consisting of 4 statements for each indicator with 5 options for each research instrument. Apart from the questionnaire method, research data was collected through random interviews and structured observation. Based on data analysis, students' imagination skills were highest in the playing with possibilities indicator at 81.05 in cycle 3. Meanwhile, students' imagination skills were lowest in the using intuitions indicator at 35.75 in cycle 1. In general, simple gamification activities were able to increase students' imagination skills between 10% - 40%.